Never smokers with lung cancer in Morocco: epidemiology and gender differences - Ouassima Erefai; Abdelmajid Soulaymani; Abdelrhani Mokhtari; Hinde Hami (International Journal of Public Health Science (IJPHS), 2022)
Even through smoking is a definite risk factor for lung cancer, it is possible for people who have never smoked to suffer lung cancer. This research aimed to describe the epidemiology of lung cancer in never smokers in Morocco. Also, an assessment of differences between men and women never smokers was performed. The researchers analyzed retrospectively all patients diagnosed with lung cancer between 2014 and 2017. The results showed that of 606 patients, 157 (25.9%) were never smokers. Of these, 79 patients (50.32%) were women. Women were more likely to be younger (p=0.034), had adenocarcinoma (p=0.046), and being in advanced stage of the disease (p=0.032). Men were more exposed to professional carcinogens (p<0.001). Tuberculosis was the most frequent previous lung disease in never smokers, but no difference was noted between men and women. Performance status and comorbidities did not vary by gender. Never smokers in Morocco represent a significant proportion of lung cancer. Evident epidemiologic differences are found between men and women never smokers, notably, age, histological type and risk factor exposure.